Changes in the composition of triacylglycerols in the fat bodies of bumblebee males during their lifetime - Jiroš, Pavel; Cvačka, Josef; Hanus, Robert; Kindl, Jiří; Kofroňová, Edita; Valterová, Irena (Lipids, 2011)
The age-dependent changes in the composition of triacylglycerols (TAG) in the fat bodies of bumblebee males were studied using HPLC/MS. Two related species (Bombus terrestris and B. lucorum) were compared, with the age of the males being 0-30 days. The total amount of TAG in B. lucorum was about 2.7 times higher than that in B. terrestris for all of the ages studied. One to three-day-old males had the highest content of TAG in their fat bodies (1.6-2.3 mg/individual in B. terrestris and 3.8-4.2 mg/individual in B. lucorum). The analytical data show different patterns in both species. The qualitative composition of fatty acids in TAG was similar, but the mean relative abundance between B. terrestris and B. lucorum differed: 14:0, 7 and 14%; 16:0, 20 and 44%; 18:3, 62 and 23%; 18:1, 3 and 8%, respectively (the data is based on a GC/MS integration). A statistical evaluation of the dynamic changes in the TAG composition revealed that in B. terrestris different age classes were well separated according to their TAG composition while in B. lucorum the TAG did not change substantially during the male's life. The TAG analyses provide more precise information on the differences between the classes studied than the FA composition alone.
Keywords: Male; triglyceridy; Animals; tukové těleso; Age Factors; hmotnostní spektrometrie; Mass Spectrometry; Fat Body; mastné kyseliny; mužské pohlaví; včely; věkové faktory; Fatty Acids; Principal Component Analysis; zvířata; multivariační analýza; Bees; Triglycerides; Multivariate Analysis; analýza hlavních komponent